2019
DOI: 10.2903/sp.efsa.2019.en-1704
|View full text |Cite
|
Sign up to set email alerts
|

EFSA's activities on emerging risks in 2018

Abstract: The main objectives of EFSA's activities on emerging risks are: (i) to identify emerging risks in the areas within the remit of EFSA; and (ii) to develop and improve emerging risk identification methodologies and approaches. The current technical report summarises the activities of all groups involved in the emerging risk identification procedure, the issues identified in the course of 2018, a description of methodologies being developed and collaborative activities.EFSA networks of knowledge contributing to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Article 34 of the EU Food law (EC, 2002) requests EFSA to draft monitoring procedures with respect to systematically searching for, collecting, collating, and analysing information and data with a view to the identification of emerging risks in the fields within its mission (Afonso et al, 2019).…”
Section: The Efsa Emerging Risks Identification Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Article 34 of the EU Food law (EC, 2002) requests EFSA to draft monitoring procedures with respect to systematically searching for, collecting, collating, and analysing information and data with a view to the identification of emerging risks in the fields within its mission (Afonso et al, 2019).…”
Section: The Efsa Emerging Risks Identification Processmentioning
confidence: 99%
“…It was concluded that a systematic approach to the identification of emerging issues based on experts' networks is the major strength of the procedure. However, some weaknesses were identified (Afonso et al, 2019). Those which have triggered the development of the CLEFSA project are listed below:…”
Section: Present Weaknesses and Opportunities Leading To The Clefsa P...mentioning
confidence: 99%